Single phase matrix converter operate as rectifier controlled by Xilinx FPGA: article / Mohd Nasrul Hisyam Mat Ruf - Mat Ruf, Mohd Nasrul Hisyam (Universiti Teknologi MARA (UiTM), 2011)
This paper presents a topology of Single Phase Matrix Converter (SPMC) that use to operate as a rectifier (AC-DC). Pulse Width Modulation (PWM) was used as a controlled signal with respect to variation of Modulation Index to synthesize the output DC voltage. IGBT was used as a power switching devices with bidirectional switch configuration to study the behavior of the converter. Computer simulation model was developed by using MATLAB/Simulink (MLS). XILINX Field Programmable Gate Array (FPGA) was used to develop Pulse Width Modulation (PWM) according to switching strategies. The selected simulation results of MATLAB/Simulink (MLS) and XILINX FPGA were presented to verify the proposed switching strategies